Answer:
32
Step-by-step explanation:
n(A∪B)=n(A)+n(B)−n(A∩B)−−−−−−−(1)
Given n(A)= ? we represent with x
n(B)= 16
n(A∪B) = 32
Substituting in equation 1 to get n(A)
32 = n(A) + 9 − 9
⇒n(A) = 32 − 0
n(A) = 32
to confirm this we put the values into the formula below
n(A∪B)=n(A)+n(B)−n(A∩B)−−−−−−−(1)
32 = 32 + 9 - 9
<span>when p = -24 and q = 4. p/2q= -24/8 = -3 </span>
No because adding the two fives will give you a 10 and 10 is greater than 3
Answer:
+2
Step-by-step explanation:
+ and - cancel. We have 5 + and 3 - so that leaves us with 2 + so the answer is +2.
Answer: See explanation
Step-by-step explanation:
15.) -7x + 6 (x - 8/2) - 2(x + 3) + 10
-7x + 6 (x - 4) - 2(x + 3) + 10
-7x + 6x - 24 - 2x - 6 + 10
Bring like terms together
-7x + 6x - 2x - 24 - 6 + 10
-3x - 20
16.) B, C, D
B. 3 (x + 2) + 4x
3x + 6 + 4x = 7x + 6
C. -2 + 4(x + 3)
-2 + 4x + 12 = 4x + 10
D. 3x + 5(x - 1)
3x + 5x - 5
8x - 5
17.) A, B, D
A. 1/5(x - 50)
1/5x - 10
B. 1/6(-x + 12)
-1/6x + 2
D. 1/2(x + 16)
1/2x + 8